Acceptance and adherence to non-invasive positive pressure ventilation in people with chronic obstructive pulmonary disease: a grounded theory study - Volpato, Eleonora; Banfi, Paolo Innocente; Pagnini, Francesco (Frontiers in Psychology, 2023)
Non-Invasive Positive Pressure Ventilation (NPPV) is an established treatment for people with Chronic Obstructive Pulmonary Disease (COPD), but it is often improperly used or rejected. The patterns of acceptance and adherence to NPPV, conceiving constraints, and strengths related to its adaptation have not been explored from a qualitative perspective yet. This study aims to qualitatively explore patterns of adaptation to NPPV in people affected by COPD and to identify the core characteristics and the specific adaptive challenges during the adaptation process. Forty-two people with moderate or severe COPD were recruited and 336 unstructured interviews were conducted. A Constructivist Grounded Theory was used to gather and analyze data: the transcriptions were mutually gathered in open, selective, and theoretical phases, with open, selective, and theoretical coding, respectively. The analysis resulted in a non-linear and dynamic process, characterized by three phases: deciding, trying NPPV, and using NPPV. The patterns revealed that positive and negative NPPV experiences, together with beliefs, emotions, stressful mental states, and behaviors result in different acceptance and adherence rates. These findings may be helpful to implement new care strategies to promote acceptance and adherence to NPPV.